THU0408 Gout is an important predictor of work disability in both men and women. (15th June 2017) - Sigurdardottir, V; Drivelegka, P; Svärd, A; Jacobsson, LT; Dehlin, M
Abstract : Background: Gout is the most common form of inflammatory arthritis with a prevalence of 1.5% in our area in the age group 50–59 years (1). Gout has a substantial association with several comorbidities. Studies on the impact of gout on work disability on a population level are scarce. Objectives: The primary objective of the study was to investigate if gout was a predictor of work absenteeism exceeding 90 days in a calendar year, controlling for comorbidites and socioeconomic status in men and women separately. Another aim of the study was to explore if urate lowering therapy (ULT) attenuated the risk of work disability for gout cases. Methods: Gout cases were defined in the population based health care database (VEGA) of the Western Swedish Health Care Region (WSHCR) by having a first diagnosis of gout in the years 2003–2009 by ICD-10 codes (M10 and M14.0) in VEGA. Cases were included if their age at the time of diagnosis of gout was ≤62 years. Five controls for each case, matched for age, sex and place of residence were chosen from the census register by Statistics Sweden. Individuals with any work disability in the year before the index year were excluded from analysis. Data on predefined comorbidities registered previous to the index year was collected from VEGA by ICD-10 codes. Data on prescribed medications was collected from the national prescription database. Data on educational level, income and number of days per calendar year with sick-leave and disability pension was provided by Statistics Sweden. Conditional logistic regression taking into account the 1-to-5 matched design of the study was performed in individuals without work disability in the year before the index date for the outcome of ≥25% (≥90 days) work disability in the year after the index year. Possible predictors of work disability for gout cases were analyzed using logistic regression Results: 3068 incident gout cases (females N=554 (18%)) of working age without prior work disability were matched to 15, 077 population controls. After matching, 3258 controls with prior work disability were excluded leaving 11, 819 controls for analysis. Of the women with gout, 69 (12.5%) became ≥25% work disabled in the year after the index-year as opposed to 117 (6.1%) of the female controls, p<0, 0001. 163 men with gout (6, 5%) became ≥25% disabled vs. 377 (3.8%) of male controls, p<0, 0001. After adjusting for comorbidities and educational level gout increased the risk of work disability to a similar extent for men (OR 1.4, 95% CI 1.2–1.8) and women (OR 1.9, 95% CI 1.4–2.6). Cardiovascular and renal comorbidity as well as alcoholism, female sex and low educational level (less than 12 years) were important predictors of work disability in gout patients whereas receiving ULT during the time period being studied did not attenuate the risk (OR 0.8, 95% CI 0.5–1.1). Conclusions: Gout is a significant independent predictor of work disability in both men and women. ULT did not attenuate the risk of work disability early after diagnosis for gout cases in this study, possibly explained by under-prescribing and sub-optimal dosage as previously shown in our region (1). References: Dehlin M, Drivelegka P, Sigurdardottir V, Svard A, Jacobsson LT. Incidence and prevalence of gout in Western Sweden. Arthritis research & therapy. 2016;18:164. Disclosure of Interest: None declared